Rozwiąż poniższe równania
1) 3(d-6)=18
2) e+8/2=5
3) (8-f):4=6
4) -5g+3=7g+8
5) 4h-(2h-7)=9
6) 6i-3=2-(i+20)


Odpowiedź :

Odpowiedź:

[tex]1) \\\\3(d-6)=18\\d-6=6\\d=6+6\\\\d=12\\\\\\2)\\\\ e+\frac{8}{2} =5\\e+4=5\\\\\\3) \\\\(8-f):4=6\\\frac{8f}{4}=4\\ 8-f=24\\-f=24-8\\-f=16\\\\\\f=-16\\\\\\4)\\\\ -5g+3=7g+8\\-5g-7g=8-3\\-12g=5\\\\\\g=-\frac{5}{12}\\\\\\5)\\\\4h-(2h-7)=9\\4h-2h+7=9\\2h+7=9\\2h=9-7\\2h=2\\\\h=1[/tex]

[tex]6)\\\\6i-3=2-(i+20)\\6i-3=2-i-20\\6i-3=-18-i\\6i+i=-18+3\\7i=-15\\\\\\i=-\frac{15}{7}[/tex]

1.

[tex]3(d-6) = 18 \ \ /:3\\\\d-6 = 6 \ \ |+6\\\\\boxed{d = 12}[/tex]

2.

[tex]e + \frac{8}{2} = 5\\\\e + 4 = 5 \ \ |-4\\\\\boxed{e = 1}[/tex]

3.

[tex](8-f):4 = 6\\\\2-\frac{f}{4} = 6 \ \ |-2\\\\-\frac{f}{4} = 4 \ \ |\cdot(-4)\\\\\boxed{f = -16}[/tex]

4.

[tex]-5g + 3 = 7g + 8\\\\-5g-7g = 8-3\\\\-12g = 5 \ \ /:(-12)\\\\\boxed{g = -\frac{5}{12}}[/tex]

5.

[tex]4h - (2h-7) = 9\\\\4h-2h +7 = 9 \ \ |-7\\\\2h = 2 \ \ /:2\\\\\boxed{h = 1}[/tex]

6.

[tex]6i - 3 = 2-(i+20)\\\\6i-3 = 2-i-20\\\\6i+i = -18+3\\\\7i = -15 \ \ /:7\\\\i = -\frac{15}{7}\\\\\boxed{i = -2\frac{1}{7}}[/tex]